2015
DOI: 10.1002/ece3.1556
|View full text |Cite
|
Sign up to set email alerts
|

Historical comparisons reveal multiple drivers of decadal change of an ecosystem engineer at the range edge

Abstract: Biogenic reefs are important for habitat provision and coastal protection. Long-term datasets on the distribution and abundance of Sabellaria alveolata (L.) are available from Britain. The aim of this study was to combine historical records and contemporary data to (1) describe spatiotemporal variation in winter temperatures, (2) document short-term and long-term changes in the distribution and abundance of S. alveolata and discuss these changes in relation to extreme weather events and recent warming, and (3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 51 publications
3
61
1
1
Order By: Relevance
“…These polychaetes are widely distributed along the European Atlantic coast, from Ireland to the south of Morocco (Firth et al 2015) and punctually in the Mediterranean Sea (Sparla et al 1992;Gambi et al 1996;Nicoletti et al 2001). S. alveolata reefs normally grow parallel to the coastline and in the direction of main tidal currents (Dubois et al 2006), and they usually develop in the intertidal or shallow subtidal habitat (De Grave and Whitaker 1997).…”
Section: Introductionmentioning
confidence: 99%
“…These polychaetes are widely distributed along the European Atlantic coast, from Ireland to the south of Morocco (Firth et al 2015) and punctually in the Mediterranean Sea (Sparla et al 1992;Gambi et al 1996;Nicoletti et al 2001). S. alveolata reefs normally grow parallel to the coastline and in the direction of main tidal currents (Dubois et al 2006), and they usually develop in the intertidal or shallow subtidal habitat (De Grave and Whitaker 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Piccioni et al, 1988) may be responsible, at least in part, for such biogeographic patterns. In non-Mediterranean regions, the majority of studies reported the exclusive occurrence of S. alveolata (e.g., Wilson, 1976;Dubois et al, 2002;Plicanti et al, 2016) or S. spinulosa (e.g., Hendrick and Foster-Smith, 2006), with the first species normally being more common and abundant in the intertidal environment (e.g., Firth et al, 2015), while the second in the subtidal environment (e.g., Pearce et al, 2014). In some cases, coexisting S. alveolata and S. spinulosa have been recorded (e.g., Wilson, 1970aWilson, , 1970b, but not at the small scale documented in the Sicily Channel.…”
Section: Discussionmentioning
confidence: 99%
“…Muller and Stone, 2001;Wolff et al, 2016) and is modelled to further increase in the near future due to climate change (Webster et al, 2005;Sriver and Huber, 2006;Trapp et al, 2007). The tube-building activity of Sabellaria may effectively repair small damaged areas of the reef within weeks or months (Cunningham et al, 1984;Vorberg, 2000;Plicanti et al, 2016), but heavier impacts may take years up to decades (Firth et al, 2015) to recover depending on temporally variable processes, such as larval supply (Gruet, 1986;Ayata et al, 2009). Permanent changes to the structure of the reef are also reported (Gibb et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on DELOS, the European Union-funded THESEUS (www.theseusproject.eu) and URBANE (www.urbaneproject.org) projects progressed our understanding of the processes underpinning the patterns of biodiversity on artificial structures at a range of spatial scales from small (mm-cm) (e.g. Bracewell et al, 2013, Coombes et al, 2013, Coombes et al, 2015, medium (cm-m) (Martins et al, 2010;Firth et al, 2013bFirth et al, , 2014a) and large geographic scales (Firth et al, 2014a(Firth et al, , 2015.…”
Section: Biodiversity On Artificial Structures Of Plymouth Soundmentioning
confidence: 99%